A combination of transcriptomics and epigenomics identifies genes and regulatory elements involved in embryonic tail development in the mouse - Yong-Xuan Chen; Xiu-Ping Zhang; David N. Cooper; Dong-Dong Wu; Wan-Dong Bao (BMC Biology)
Abstract Background The post-anal tail is a common physical feature of vertebrates including mammals. Although it exhibits rich phenotypic diversity, its development has been evolutionarily conserved as early as the embryonic period. Genes participating in embryonic tail morphogenesis have hitherto been widely explored on the basis of experimental discovery, whereas the associated cis-regulatory elements (CREs) have not yet been systematically investigated for vertebrate/mammalian tail development. Results Here, utilizing high-throughput sequencing schemes pioneered in mice, we profiled the dynamic transcriptome and CREs marked by active histone modifications during embryonic tail morphogenesis. Temporal and spatial disparity analyses revealed the genes specific to tail development and their putative CREs, which facilitated the identification of novel molecular expression features and potential regulatory influence of non-coding loci including long non-coding RNA (lncRNA) genes and CREs. Moreover, these identified sets of multi-omics data supply genetic clues for understanding the regulatory effects of relevant signaling pathways (such as Fgf, Wnt) dominating embryonic tail morphogenesis. Conclusions Our work brings new insights and provides exploitable fundamental datasets for the elucidation of the complex genetic mechanisms responsible for the formation of the vertebrate/mammalian tail.